Positive electrode active material and preparation method thereof, positive electrode sheet, battery and electrical equipment
The positive electrode active material with controlled X-ray diffraction peak ratios and element doping, along with inorganic reducing agents, stabilizes Fe 2+ and reduces impurities, enhancing thermal and cycle stability in sodium-ion batteries.
Patent Information
- Application Number
- CN202410544773.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-04-30
- Publication Date
- 2025-01-03
- Estimated Expiration
- 2044-04-30
AI Technical Summary
Sodium ferrous sulfate carbon composite materials for sodium-ion batteries suffer from poor thermal stability due to Fe 2+ oxidation to Fe 3+, leading to impurities like Fe3O4 or Fe2O3, which affect recycling performance and cycle stability.
A positive electrode active material with specific X-ray diffraction peak intensity ratios and element doping, combined with inorganic reducing agents, to stabilize Fe 2+ and reduce impurities, enhancing thermal stability and cycle performance.
The solution effectively maintains Fe 2+ in the material, reducing impurities and improving specific capacity and cycle stability, ensuring good structural stability and air stability.
Smart Images

Figure CN118335973B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of sodium ion batteries, and in particular to a positive electrode active material and a preparation method thereof, a positive electrode sheet, a battery and an electrical device. Background Art
[0002] Lithium-ion batteries are currently widely used in electric vehicles, laptops, mobile phones, and other electronic products, becoming increasingly intertwined with human production and daily life. However, as lithium resource prices fluctuate, low-cost sodium-ion batteries, which operate on a similar principle, are gaining widespread attention. They are expected to partially replace lithium-ion batteries in low-speed electric vehicles and energy storage, making a significant contribution to further expanding the battery market.
[0003] Among them, similar to lithium iron phosphate cathode materials in lithium-ion batteries, polyanion materials show lower cost and best cycle performance among several cathode materials for sodium-ion batteries. In particular, sodium ferrous sulfate carbon composite materials (Na 2+2x Fe 2-x (SO4)3@C) has low main raw material cost, low sintering energy consumption and a high discharge voltage platform, and has good application prospects.
[0004] However, this type of material has poor thermal stability. Even after undergoing a low-temperature sintering process under inert atmosphere protection, it is still easy to contain Fe. 3+ Fe3O4 or Fe2O3 impurities. For example, in the literature published by Li et al. (J. Mater. Chem. A, 2019, 7, 14656-14669, DOI: 10.1039 / c9ta03089a), Na6Fe5(SO4)8@CNTs materials with high initial discharge capacity and discharge voltage were prepared using solid phase mixing and low temperature sintering process. However, after testing, more than 20% of Fe 2+ Oxidized to Fe 3+ , which seriously affects the recycling performance of the material.
[0005] To protect Fe 2+ It is not oxidized. In the prior art, metal powder (such as Fe) is added during the ball milling process to 2+ However, this also increases the risk of magnetic foreign matter and impurities in the product. In addition, there is also a method of adding an organic antioxidant (such as ascorbic acid, etc.) to a Na2SO4 and FeSO4·nH2O solution and then preparing a precursor to perform Fe 2+However, organic materials are easily decomposed by heat, and it is difficult to maintain the antioxidant effect during the subsequent sintering process. In addition, low-temperature sintering is not conducive to their effective carbonization, which acts as an impurity and has an adverse effect on the performance of the material. Therefore, it is urgent to provide a new preparation method that can solve the problem of Fe 2+ oxidation problem while reducing the introduction of impurities. Summary of the Invention
[0006] The present invention aims to solve one of the technical problems in the related art to at least a certain extent. To this end, the present invention provides a positive electrode active material and a preparation method thereof, aiming to solve the problem of Fe 2+ It solves the oxidation problem of lithium ion batteries, reduces the introduction of impurities, and improves the specific capacity and cycle stability of the material.
[0007] To this end, a first aspect of the present invention provides a positive electrode active material, wherein the positive electrode active material is an iron-based sulfate sodium ion battery positive electrode material, and the X-ray diffraction pattern of the positive electrode active material has a first characteristic peak in the range of 34.9° to 35.3° and a second characteristic peak in the range of 35.3° to 35.5°;
[0008] The peak intensity I1 of the first characteristic peak and the peak intensity I2 of the second characteristic peak satisfy: 1.1≤I1 / I2≤1.5.
[0009] The first characteristic peak mentioned above belongs to the (-132) crystal plane of the positive electrode active material, and the second characteristic peak is a composite characteristic peak, which is produced by the overlap of the characteristic peak of the (112) crystal plane and the strongest characteristic peak of the (311) crystal plane of Fe3O4 at 35.4°. Fe3O4 is produced by the side reaction of the decomposition of FeSO4. Therefore, the higher the relative peak intensity of the second characteristic peak, the stronger the side reaction occurred during the preparation process of the positive electrode active material, the more impurities there are, and the less available Fe 2+ / Fe 3+ When the peak intensity ratio of the first characteristic peak to the second characteristic peak in the X-ray diffraction pattern (XRD pattern) of the positive electrode active material meets the above conditions, it indicates that the Fe in the positive electrode active material exists mainly in the form of Fe 2+ , and Fe 3+ The mass percentage in the material is less than 1.5%, which greatly reduces the Fe3O4 impurity phase in the positive electrode active material. 3+ The content of MgO increases the reactivity of the positive electrode active material.
[0010] According to an embodiment of the present invention, the peak intensity of the first characteristic peak of the positive electrode active material after being left in an open environment at a temperature of 25° C. and a relative humidity of 30% for 24 hours is 1’The peak intensity of the second characteristic peak I 2’ satisfy:
[0011] 1.05≤I 1’ / I 2’ ≤1.4;
[0012]
[0013] This shows that the positive electrode active material can also ensure the Fe 2+ Not oxidized, Fe 3+ The content remains basically unchanged, and the positive electrode active material has good structural stability.
[0014] According to an embodiment of the present invention, the peak intensity I1 of the first characteristic peak and the peak intensity I2 of the second characteristic peak satisfy the following conditions: 1.2≤I1 / I2≤1.4. This indicates that the Fe in the positive electrode active material exists mainly in the form of Fe 2+ , Fe 3+ The mass ratio in the material is lower.
[0015] According to an embodiment of the present invention, 1.1≤I 1’ / I 2’ ≤1.25;
[0016] When the positive electrode active material meets the above conditions, it is more conducive to storage and has good structural stability.
[0017] According to an embodiment of the present invention, the positive electrode active material satisfies at least one of the following conditions:
[0018] The positive electrode active material D 50 4-10μm;
[0019] The positive electrode active material D 100 Satisfies: 6μm<D 100 <20μm;
[0020] The specific surface area of the positive electrode active material is 5-25m 2 / g.
[0021] According to an embodiment of the present invention, the positive electrode active material has a chemical formula shown in formula (1):
[0022] Na 2x Fe 2-y M y (SO4) (2+x-z) (SO3) z @C(1)
[0023] Among them, 1≤x≤2.04, preferably 1≤x≤1.4; 0≤y≤0.2; 0<z≤0.04, preferably 0<z≤0.03;
[0024] M is selected from at least one of Mn, Co, Ni, Mg, Cu, and Zn.
[0025] Thus, the crystal structure of the positive electrode active material is improved by element doping, the thermal stability of the material is enhanced, and the side reaction of the positive electrode active material decomposing itself to produce Fe3O4 or Fe2O3 impurities is suppressed. At the same time, the material structure contains SO3 2- , and also ensure that the Fe content in the material is 2+ protection, and improve the air stability of the material structure. Doping of transition metal elements and SO3 2- The presence of Fe in the positive electrode active material 3+ The content is extremely low and it exhibits high specific capacity and good cycle stability and storage performance.
[0026] A second aspect of the present invention provides a method for preparing a positive electrode active material, the method comprising:
[0027] (1) preparing a reducing agent solution, mixing an inorganic conductive carbon material with the reducing agent solution to obtain a mixed solution 1;
[0028] (2) mixing Na2SO4, FeSO4·7H2O, and optionally sulfate with the mixed solution 1 to obtain a mixed solution 2;
[0029] (3) spray drying the mixed solution 2 to obtain a positive electrode active material precursor;
[0030] (4) sintering the positive electrode active material precursor to obtain the positive electrode active material;
[0031] Wherein, the reducing agent in the reducing agent solution is NaHSO3 and / or Na2S2O5;
[0032] The sulfate is used to provide the M element, and the M element is selected from at least one of Mn, Co, Ni, Mg, Cu, and Zn.
[0033] The present invention provides a method for improving the thermal stability of positive electrode active materials by synergistic action of element doping and inorganic reducing agents, and 2+ The element doping improves the problem of the crystal structure of sodium ferrous sulfate materials being easily decomposed by heat, effectively reducing impurities. The introduction of inorganic reducing agents, from the synthesis to the storage process, has a long-term effect on Fe 2+The synergistic effect of the two methods is of great significance for the production of high-quality polyanion sodium cathode active materials.
[0034] According to an embodiment of the present invention, the mass of the solvent in the reducing agent solution in step (1) is 2-3 times the mass of the FeSO4·7H2O added in step (2).
[0035] According to an embodiment of the present invention, in step (1), the inorganic conductive carbon material includes at least one selected from graphene, reduced graphene oxide, conductive graphite, acetylene black, Ketjen black, mesoporous carbon, and carbon nanotubes.
[0036] According to an embodiment of the present invention, in step (2), the molar ratio of Na2SO4, FeSO4·7H2O and sulfate is δ:2-y:y;
[0037] Among them, 0.96≤δ≤2; 0≤y≤0.2.
[0038] According to an embodiment of the present invention, the molar ratio of sodium element to Na2SO4 in the reducing agent is 2n:δ;
[0039] Among them, 0<n≤0.04.
[0040] According to an embodiment of the present invention, in step (2), the mass ratio of the Na2SO4, FeSO4·7H2O and sulfate after complete dehydration to the inorganic conductive carbon material is 100:(0.5-10).
[0041] According to an embodiment of the present invention, in step (3), the spray drying conditions include:
[0042] The inlet air temperature is 130-160℃; the outlet air temperature is not less than 80℃.
[0043] According to an embodiment of the present invention, in step (3), the D of the positive electrode active material precursor 50 4-10μm;
[0044] The positive electrode active material precursor D 100 Satisfies: 6μm<D 100 <20μm.
[0045] According to an embodiment of the present invention, in step (4), the sintering conditions include: sintering at 300-380° C. for 8-20 hours.
[0046] A third aspect of the present invention provides a positive electrode plate, which includes the positive electrode active material described in the first aspect or the positive electrode active material prepared by the preparation method described in the second aspect.
[0047] A fourth aspect of the present invention provides a battery, comprising the positive electrode sheet according to the third aspect.
[0048] A fifth aspect of the present invention provides an electrical device, which includes the battery described in the fourth aspect.
[0049] Additional aspects and advantages of the present invention will be set forth in part in the description which follows and, in part, will be obvious from the description which follows, or may be learned by practice of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS
[0050] The above and / or additional aspects and advantages of the present invention will become apparent and readily understood from the following description of the embodiments with reference to the accompanying drawings, in which:
[0051] Figure 1 The SEM image of the spray material precursor obtained in Example 1 of the present invention is shown;
[0052] Figure 2 shows an SEM image of the positive electrode active material obtained in Example 1 of the present invention;
[0053] Figure 3 A comparison diagram showing the XRD pattern of the positive electrode active material obtained in Example 1 of the present invention and the standard spectrum of the crystal structure of the sodium ferrous sulfate material (wherein the standard spectrum is derived from the document DOI: 10.1039 / C9TA00116F (J. Mater. Chem. A, 2019, 7, 8226–8233)) is shown;
[0054] Figure 4 A comparison diagram showing the XRD pattern of the positive electrode active material obtained in Example 1 of the present invention after being placed in an open system for 24 hours and the standard spectrum of the crystal structure of the sodium ferrous sulfate material (wherein the standard spectrum is derived from the document DOI: 10.1039 / C9TA00116F (J. Mater. Chem. A, 2019, 7, 8226–8233)) is shown;
[0055] Figure 5 The constant current charge and discharge curve of the sodium ion battery prepared based on the positive electrode active material in Example 1 of the present invention at 0.1C is shown;
[0056] Figure 6 The figure shows the cycle curve of the sodium ion battery prepared based on the positive electrode active material in Example 1 of the present invention at 1C;
[0057] Figure 7 shows an SEM image of the positive electrode active material obtained in Example 7 of the present invention;
[0058] Figure 8The figure shows the gelation phenomenon that occurs when preparing the positive electrode slurry in Example 7 of the present invention;
[0059] Figure 9 shows the XRD pattern of the positive electrode active material obtained in Comparative Example 2 of the present invention;
[0060] Figure 10 The XRD pattern of the positive electrode active material obtained in Comparative Example 2 of the present invention after being placed in an open system for 24 hours is shown;
[0061] Figure 11 The XRD pattern of the positive electrode active material obtained in Comparative Example 4 of the present invention is shown. DETAILED DESCRIPTION
[0062] The following embodiments of the technical solution of the present invention are described in detail. The following embodiments are only used to more clearly illustrate the technical solution of the present invention and are therefore only used as examples and are not intended to limit the scope of protection of the present invention.
[0063] References herein to "embodiments" mean that a particular feature, structure, or characteristic described in connection with the embodiments may be included in at least one embodiment of the present invention. The appearance of this phrase in various places in the specification does not necessarily refer to the same embodiment, nor does it constitute a separate or alternative embodiment that is mutually exclusive of other embodiments. It is understood, both explicitly and implicitly, by those skilled in the art that the embodiments described herein may be combined with other embodiments.
[0064] " range " disclosed in the present invention is limited in the form of lower limit and upper limit, and given range is limited by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundary of special range. The scope limited in this way can be to include end value or not include end value, and can be arbitrarily combined, that is, any lower limit can form a range with any upper limit combination. For example, if the scope of 60-120 and 80-110 is listed for specific parameters, it is understood that the scope of 60-110 and 80-120 is also expected. In addition, if the minimum range value 1 and 2 are listed, and if the maximum range value 3,4 and 5 are listed, then the following range can all be expected: 1-3, 1-4, 1-5, 2-3, 2-4 and 2-5. In the present invention, unless otherwise specified, the numerical range " ab " represents the abbreviation of any real number combination between a and b, wherein a and b are all real numbers. For example, a numerical range of "0-5" indicates that all real numbers between "0-5" are listed herein, and "0-5" is simply an abbreviation for these numerical combinations. Furthermore, when a parameter is expressed as an integer ≥ 2, this is equivalent to disclosing that the parameter is, for example, an integer of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.
[0065] Unless otherwise specified, all embodiments and optional embodiments of the present invention can be combined with each other to form new technical solutions.
[0066] Unless otherwise specified, all technical features and optional technical features of the present invention can be combined with each other to form a new technical solution.
[0067] Unless otherwise specified, all steps of the present invention may be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), which means that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, the method may further include step (c), which means that step (c) may be added to the method in any order, for example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.
[0068] A first aspect of the present invention provides a positive electrode active material, wherein the positive electrode active material is an iron-based sulfate sodium ion battery positive electrode material, and the X-ray diffraction pattern of the positive electrode active material has a first characteristic peak in the range of 34.9° to 35.3° and a second characteristic peak in the range of 35.3° to 35.5°;
[0069] The peak intensity I1 of the first characteristic peak and the peak intensity I2 of the second characteristic peak satisfy: 1.1≤I1 / I2≤1.5.
[0070] The existing technology for positive electrode active materials has poor thermal stability and is prone to Fe 3+ In order to solve the problem of Fe3O4 or Fe2O3 impurities, metal powder (such as Fe) is often added during the preparation process to 2+ reduction protection, but this will also increase the risk of magnetic foreign matter and impurities in the product. In addition, organic antioxidants can be added during the preparation process, but they are easy to decompose, and it is difficult to maintain the antioxidant effect during the subsequent calcination process. At the same time, low-temperature sintering is not conducive to its effective carbonization, and as an impurity, it has an adverse effect on the performance of the material. The present invention found that when the peak intensity ratio of the first characteristic peak and the second characteristic peak in the X-ray diffraction pattern (XRD pattern) of the positive active material meets the above conditions, it indicates that the existence form of Fe in the positive active material is mainly Fe 2+ , and Fe 3+ The mass percentage in the material is less than 1.5%, which greatly reduces the Fe3O4 impurity phase in the positive electrode active material. 3+The content of FeSO4 increases the reactivity of the positive electrode active material. This is because the first characteristic peak belongs to the (-132) crystal plane of the positive electrode active material, and the second characteristic peak belongs to the characteristic peak of the (112) crystal plane, which produces FeSO4 by decomposition. 3+ The composite characteristic peak is generated by the overlap of the strongest characteristic peak of the (311) crystal plane of Fe3O4 at 35.4°. Therefore, the higher the relative peak intensity of the second characteristic peak, the stronger the side reaction occurs during the preparation of the positive electrode active material, the more impurities there are, and the less available Fe 2+ / Fe 3+ The number of charge pairs decreases, resulting in a decrease in the specific capacity and cycle performance of the positive electrode active material.
[0071] According to a specific embodiment of the present invention, the peak intensity of the first characteristic peak of the positive electrode active material after being left in an open environment at a temperature of 25° C. and a relative humidity of 30% for 24 hours is 1’ The peak intensity of the second characteristic peak I 2’ satisfy:
[0072] 1.05≤I 1’ / I 2’ ≤1.4;
[0073]
[0074] When the positive electrode active material meets the above conditions, it indicates that the material can also be protected by the reducing agent during storage, the Fe3+ content remains substantially unchanged, and the structural stability of the material is good.
[0075] According to a specific embodiment of the present invention, the peak intensity I1 of the first characteristic peak and the peak intensity I2 of the second characteristic peak satisfy the following conditions: 1.2≤I1 / I2≤1.4. This indicates that the Fe in the positive electrode active material exists mainly in the form of Fe 2+ , Fe 3+ The mass ratio in the material is lower,
[0076] According to a specific embodiment of the present invention, 1.1≤I 1’ / I 2’ ≤1.25;
[0077] When the positive electrode active material meets the above conditions, it is more conducive to storage and has good structural stability.
[0078] The above definition of relative humidity is the percentage of the actual water vapor density contained in a unit volume of air (represented by d1) and the saturated water vapor density at the same temperature (represented by d2), that is, RH (%) = d1 / d2 × 100%. Another calculation method is: the percentage of the actual air water vapor pressure (represented by p1) and the saturated water vapor pressure at the same temperature (represented by p2), that is, RH (%) = p1 / p2 × 100%.
[0079] According to a specific embodiment of the present invention, the positive electrode active material satisfies at least one of the following conditions:
[0080] The positive electrode active material D 50 4-10μm;
[0081] The positive electrode active material D 100 Satisfies: 6μm<D 100 <20μm;
[0082] The specific surface area of the positive electrode active material is 5-25m 2 / g.
[0083] The morphology of the positive electrode active material is not particularly limited, and is preferably a regular spherical particle. The particle size range of the positive electrode active material is preferably a small particle size range, preferably the D of the positive electrode active material 50 4-10μm, as some specific examples, such as D 50 The particle size of the precursor is 4μm, 5μm, 6μm, 7μm, 8μm, 9μm, 10μm, etc. The particles with regular morphology are produced. Because the particle size of the precursor will be deferred to the positive electrode material, it will affect the electrochemical performance. Therefore, it is necessary to control the D 50 The better electrical properties can be achieved by adjusting the spray drying parameters during the preparation process. 100 Satisfies: 6μm<D 100 <20μm, as some specific examples, such as D 100 19μm, 18μm, 17μm, 16μm, etc.
[0084] Preferably, the specific surface area of the positive electrode active material is 5-25 m 2 / g, as some specific examples, such as a specific surface area of 5m 2 / g、6m 2 / g、7m 2 / g、8m 2 / g、9m 2 / g、10m 2 / g、11m 2 / g、12m 2 / g、13m 2 / g、14m 2 / g、15m 2 / g、16m 2 / g、17m 2 / g、18m 2 / g、19m 2 / g, 20m 2 / g, 21m 2 / g、22m 2 / g, 23m 2 / g、24m 2 / g, 25m 2 / g, etc. When the specific surface area of the positive electrode active material is 5-25m 2 / g range, the material is not prone to the adverse phenomenon of gelation during the preparation of the positive electrode slurry due to the water-absorbing property of sodium ferrous sulfate materials.
[0085] According to a specific embodiment of the present invention, the positive electrode active material has a chemical formula shown in formula (1):
[0086] Na 2x Fe 2-y M y (SO4) (2+x-z) (SO3) z @C(1)
[0087] Among them, 1≤x≤2.04, 0≤y≤0.2; 0<z≤0.04;
[0088] M is selected from at least one of Mn, Co, Ni, Mg, Cu, and Zn.
[0089] The chemical composition of the positive electrode active material includes doping elements M and SO3 2- Doping elements can improve the crystal structure of the material, enhance the thermal stability of the material, and inhibit the side reaction of sodium ferrous sulfate materials decomposing themselves to produce Fe3O4 or Fe2O3 impurities. 2- It comes from the inorganic reducing agent added during the preparation process. During the preparation process or material storage process, when the system contains oxygen, Fe 2+ It reacts first and converts into SO4 2- , so transition metal element doping and SO3 2- Synthetic protection of sodium ferrous sulfate-based carbon composite cathode materials for sodium ion batteries 3+ The content is extremely low and it exhibits high specific capacity, good cycle stability and storage performance.
[0090] The closer x is to 1 in the chemical formula, the higher the proportion of Na +The higher the material's theoretical specific capacity, the more it participates in the electrochemical reaction process of insertion / extraction. Specifically, 1≤x≤2.04. As some specific examples, x can be 1, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, 1.9, 2.0, 2.04, etc.; preferably, 1≤x≤1.4.
[0091] In the chemical formula, y corresponds to the doping level of the doping element. Doping elements can improve the structural stability of the material but have no significant effect on capacity, so a lower doping level is preferred. 0 ≤ y ≤ 0.2. For example, y can be 0, 0.1, 0.2, etc. Doping elements M include, but are not limited to, Mn, Co, Ni, Mg, Cu, and Zn.
[0092] In the chemical formula, z corresponds to the residual amount of reducing agent in the prepared positive electrode active material, which is only added in a trace amount during the preparation process. Therefore, 0<z≤0.04. As some specific examples, z can be 0, 0.01, 0.02, 0.03, 0.04, etc., preferably 0<z≤0.03. The reducing agent can be NaHSO3 and / or Na2S2O5. During the sintering process, NaHSO3 or Na2S2O5 will first be converted into Na2SO3 during the heating process. Less than Na2SO3 is a stronger reducing agent than Fe in the presence of trace oxygen. 2+ It reacts first and is converted into raw material Na2SO4. It continues to participate in the solid phase reaction with FeSO4 in the subsequent sintering process without causing other effects. If the oxygen content of the sintering atmosphere is extremely low, Na2SO3 will not be oxidized during the sintering process and can also protect Fe for a long time during the storage of the material. 2+ , improving the air stability of the material structure. Therefore, to a certain extent, the chemical formula of the positive electrode active material will change with the storage time, that is, z tends to decrease until it reaches zero.
[0093] At the same time, it can be seen from the chemical formula that the surface of the positive electrode active material is coated with a carbon material, wherein the carbon material includes but is not limited to graphene, reduced graphene oxide, conductive graphite, acetylene black, Ketjen black, mesoporous carbon and carbon nanotubes. The mass fraction of the carbon material in the positive electrode active material is 0.5-10%, as some specific examples, such as 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, 5.5%, 6%, 6.5%, 7%, 7.5%, 8%, 8.5%, 9%, 9.5%, 10%, etc. The type of conductive carbon selected for addition will have a significant effect on the specific surface area of the material, but the upper limit can be controlled by adjusting the parameter settings during the preparation process to prepare a spray material precursor with a regular morphology.
[0094] A second aspect of the present invention provides a method for preparing a positive electrode active material, the method comprising:
[0095] (1) A reducing agent solution is prepared, and an inorganic conductive carbon material is mixed with the reducing agent solution to obtain a mixed solution 1.
[0096] According to a specific embodiment of the present invention, the reducing agent in the reducing agent solution is preferably NaHSO3 and / or Na2S2O5, and the reducing agent solution is preferably an acidic solution, that is, the reducing agent is in an acidic condition during the preparation of the solution, which can effectively inhibit Fe 2+ Oxidized or hydrolyzed to maintain Fe content in subsequent batching and spraying processes 2+ stability.
[0097] According to a specific embodiment of the present invention, the specific type of the inorganic conductive carbon material is not particularly limited, and those skilled in the art can select it according to actual conditions. For example, the inorganic conductive carbon material can include at least one of graphene, reduced graphene oxide, conductive graphite, acetylene black, Ketjen black, mesoporous carbon, and carbon nanotubes.
[0098] Specifically, step (1) can be: weighing a small amount of inorganic reducing agent and adding it to an appropriate amount of deionized water, and rapidly stirring it until it is completely dissolved to obtain a uniform acidic aqueous solution with reducing agent protection;
[0099] A certain amount of one or more inorganic conductive carbon materials is weighed and added to the above acidic aqueous solution containing a reducing agent, and a mixed solution 1 with uniformly distributed carbon particles is obtained through continuous stirring and ultrasonic dispersion.
[0100] (2) Na2SO4, FeSO4·7H2O, and optional sulfate are mixed with the mixed solution 1 to obtain a mixed solution 2.
[0101] According to a specific embodiment of the present invention, the sulfate is used to provide the M element, and the M element is selected from at least one of Mn, Co, Ni, Mg, Cu, and Zn. That is, the sulfate includes but is not limited to MnSO4, CoSO4, NiSO4, MgSO4, CuSO4, ZnSO4, and their crystalline hydrates.
[0102] According to a specific embodiment of the present invention, the mass of the solvent in the reducing agent solution in step (1) is 2-3 times the mass of the FeSO4·7H2O added in step (2). The solvent includes, but is not limited to, deionized water. The solubility of FeSO4·7H2O in water at room temperature is greater than 50g. Although further addition of water is beneficial for solute dispersion and increased dissolution rate, it will reduce the spray drying efficiency and increase production costs due to water consumption.
[0103] According to a specific embodiment of the present invention, in step (2), the molar ratio of Na2SO4, FeSO4·7H2O and sulfate is δ:2-y:y.
[0104] Among them, 0.96≤δ≤2; as some specific examples, δ is 0.96, 1, 1.5, 2, etc.; 0≤y≤0.2, as some specific examples, y is 0, 0.1, 0.2, etc.
[0105] According to a specific embodiment of the present invention, the molar ratio of sodium element to Na2SO4 in the reducing agent is 2n:δ.
[0106] Here, 0<n≤0.04, as some specific examples, n is 0.01, 0.02, 0.03, 0.04, etc.
[0107] According to a specific embodiment of the present invention, the mass ratio of the Na2SO4, FeSO4·7H2O and sulfate after complete dehydration to the inorganic conductive carbon material is 100:(0.5-10), as some specific examples, such as 100:0.5, 100:1, 100:1.5, 100:2, 100:2.5, 100:3, 100:3.5, 100:4, 100:4.5, 100:5, 100:5.5, 100:6, 100:6.5, 100:7, 100:7.5, 100:8, 100:8.5, 100:9, 100:9.5, 100:10, etc. Because the intrinsic electronic conductivity of sodium ferrous sulfate materials is lower than that of other types of sodium ion battery positive electrode materials, and inhibiting the FeSO4 side reaction will also consume a small amount of carbon, more conductive carbon needs to be added when preparing the solution.
[0108] Specifically, step (2) can be: weighing an appropriate amount of anhydrous Na2SO4, FeSO4·7H2O and at least one M sulfate and adding them to the above mixed solution 1, and stirring rapidly for a long time until the raw materials in the solution are completely dissolved to obtain the mixed solution 2 to be sprayed.
[0109] (3) The mixed solution 2 is spray-dried to obtain a positive electrode active material precursor.
[0110] According to a specific embodiment of the present invention, the spray drying conditions include:
[0111] The inlet air temperature is 130-160°C, as some specific examples, such as 130°C, 140°C, 150°C, 160°C, etc., the inlet air temperature is less than 160°C, which can inhibit the rapid thermal dehydration of FeSO4 in the air into Fe(OH)SO4; the outlet air temperature is not less than 80°C, as some specific examples, such as 80°C, 90°C, 100°C, 105°C, etc., which is conducive to removing moisture and achieving a certain degree of dryness.
[0112] According to a specific embodiment of the present invention, the positive electrode active material precursor has a regular spherical particle morphology and an average particle size D 50 4-10μm, as some specific examples, such as D 50 4μm, 5μm, 6μm, 7μm, 8μm, 9μm, 10μm, etc. The maximum particle size D 100 Satisfies: 6μm<D 100 <20μm, as some specific examples, such as D 100 The particle sizes of the positive electrode active materials obtained after sintering are basically the same as those of the precursor.
[0113] Specifically, step (3) may be: subjecting the mixed solution to a spray drying process under set parameters while continuously stirring, and directly collecting the spray material precursor after the spraying is completed.
[0114] (4) Sintering the positive electrode active material precursor to obtain the positive electrode active material.
[0115] During the sintering process, NaHSO3 or Na2S2O5 will first be converted into Na2SO3 during the heating process, and some SO2 will be generated during this process. Less than Na2SO3 is a stronger reducing agent than Fe in the presence of trace oxygen. 2+ It reacts first and is converted into raw material Na2SO4. It continues to participate in the solid phase reaction with FeSO4 in the subsequent sintering process without causing other effects. If the oxygen content of the sintering atmosphere is extremely low, Na2SO3 will not be oxidized during the sintering process and can also protect Fe for a long time during the storage of the material. 2+ , improving the air stability of the material structure.
[0116] According to a specific embodiment of the present invention, the sintering process is a process in which the precursor completely removes crystallization water and undergoes a solid-phase reaction. The sintering conditions affect the residual water content, crystallization strength and impurity content of the material. The sintering conditions can be: at 300-380°C, as some specific examples, such as 300°C, 310°C, 320°C, 330°C, 340°C, 350°C, 360°C, 370°C, 380°C, etc., sintering for 8-20h, as some specific examples, such as 8h, 9h, 10h, 11h, 12h, 13h, 14h, 15h, 16h, 17h, 18h, 19h, 20h, etc. The heating rate is not particularly limited, and those skilled in the art can make a reasonable selection according to actual conditions, preferably 1-3°C / min, as some specific examples, such as 1°C / min, 1.5°C / min, 2°C / min, 2.5°C / min, 3°C / min, etc.
[0117] Specifically, step (4) can be: placing the above-mentioned spray material precursor in a furnace with a continuously inert atmosphere to carry out a low-temperature sintering process, and finally obtaining a sodium ferrous sulfate-based carbon composite sodium ion battery positive electrode material.
[0118] A third aspect of the present invention provides a positive electrode plate, which includes the positive electrode active material described in the first aspect of the present invention or the positive electrode active material prepared by the method described in the second aspect.
[0119] The positive electrode sheet generally includes a positive electrode current collector and a positive electrode active material layer disposed on the positive electrode current collector, wherein the positive electrode active material layer includes a positive electrode active material.
[0120] The positive electrode current collector may be a conventional metal foil or a composite current collector (a metal material may be disposed on a polymer substrate to form a composite current collector). As an example, the positive electrode current collector may include at least one of copper foil, aluminum foil, nickel foil, stainless steel foil, stainless steel mesh, and carbon-coated aluminum foil.
[0121] The positive electrode active material includes the positive electrode active material described in the first aspect of the present invention or the positive electrode active material prepared by the method described in the second aspect.
[0122] The positive electrode active material layer may also optionally include a conductive agent and a binder. The conductive agent is used to improve the conductivity of the positive electrode active material layer, and the binder is used to firmly bond the positive electrode active material and the binder to the positive electrode current collector. The present invention does not specifically limit the types of conductive agent and binder, and they can be selected according to actual needs.
[0123] As an example, the conductive agent may include at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene and carbon nanofibers; the binder may include at least one of polyvinylidene fluoride (PVDF), vinylidene fluoride copolymers or their modified (for example, carboxylic acid, acrylic acid, acrylonitrile, etc.) derivatives.
[0124] These materials are all commercially available.
[0125] A fourth aspect of the present invention provides a battery comprising the positive electrode sheet according to the third aspect of the present invention, thereby providing the battery with an excellent cycle life.
[0126] A battery is a battery that can be recharged to activate the active materials after discharge and continue to be used.
[0127] It is understandable that the battery proposed in the present invention is a lithium-ion battery.
[0128] Typically, a battery consists of a positive electrode, a negative electrode, a separator, and an electrolyte. During the battery's charge and discharge processes, active ions are inserted and removed between the positive and negative electrodes. The separator is placed between the positive and negative electrodes to isolate them. The electrolyte conducts ions between the positive and negative electrodes.
[0129] [Negative electrode]
[0130] In a battery, the negative electrode sheet generally includes a negative electrode current collector and a negative electrode active material layer disposed on the negative electrode current collector, wherein the negative electrode active material layer includes a negative electrode active material.
[0131] The negative electrode current collector is generally a structure or component that collects current. The negative electrode current collector can be any material suitable for use as a negative electrode current collector for lithium secondary batteries in the art, and can be a conventional metal foil or a composite current collector (for example, a metal material can be disposed on a polymer substrate to form a composite current collector). As an example, the negative electrode current collector can be copper foil or a lithium sheet.
[0132] The specific type of the negative electrode active material is not limited, and active materials known in the art that can be used for battery negative electrodes can be used, and those skilled in the art can select according to actual needs. As an example, the negative electrode active material can be a combination of one or more including but not limited to graphite, soft carbon, hard carbon, carbon fiber, mesophase carbon microbeads, silicon-based materials, tin-based materials, lithium titanate or other metals that can form alloys with lithium. Among them, the graphite can be selected from a combination of one or more of artificial graphite, natural graphite and modified graphite; the silicon-based material can be selected from a combination of one or more of elemental silicon, silicon oxide compounds, silicon-carbon composites, and silicon alloys; the tin-based material can be selected from a combination of one or more of elemental tin, tin oxide compounds, and tin alloys. These materials can all be obtained through commercial channels.
[0133] In some embodiments, to further improve the energy density of the battery, the negative electrode active material may include a silicon-based material.
[0134] The negative electrode active material layer may further include a binder, a conductive agent, and other optional auxiliary agents.
[0135] As an example, the conductive agent may include one or more of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.
[0136] As an example, the binder may include one or more of styrene-butadiene rubber (SBR), water-based acrylic resin, polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), ethylene-vinyl acetate copolymer (EVA), polyvinyl alcohol (PVA) and polyvinyl butyral (PVB).
[0137] As examples, other optional additives may include thickening and dispersing agents (eg, sodium carboxymethyl cellulose CMC-Na), and PTC thermistor materials.
[0138] [Electrolyte]
[0139] The electrolyte solution may include an electrolyte salt and a solvent.
[0140] As an example, the electrolyte salt may include one or more of sodium hexafluorophosphate (NaPF6), sodium tetrafluoroborate (NaBF4), lithium perchlorate (NaClO4), sodium bis(fluorosulfonyl)imide (NaFSI), and sodium trifluoromethanesulfonate (NaTFS).
[0141] As an example, the solvent may include at least one of ethylene carbonate (EC), propylene carbonate (PC), ethyl methyl carbonate (EMC), diethyl carbonate (DEC), dimethyl carbonate (DMC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), butylene carbonate (BC), fluoroethylene carbonate (FEC), methyl formate (MF), methyl acetate (MA), ethyl acetate (EA), propyl acetate (PA), methyl propionate (MP), ethyl propionate (EP), propyl propionate (PP), methyl butyrate (MB), ethyl butyrate (EB), 1,4-butyrolactone (GBL), sulfolane (SF), dimethyl sulfone (MSM), ethyl methyl sulfone (EMS) and diethyl sulfone (ESE).
[0142] In some embodiments, the electrolyte further includes additives. For example, the additives may include negative electrode film-forming additives, positive electrode film-forming additives, or additives capable of improving certain battery properties, such as additives that improve battery overcharge performance, additives that improve battery high-temperature performance, and additives that improve battery low-temperature performance.
[0143] [Isolation film]
[0144] As the above-mentioned isolation membrane, the present invention has no special restrictions and any known porous structure isolation membrane with electrochemical stability and mechanical stability can be selected according to actual needs. For example, it can include a combination of at least one of polyethylene, polypropylene, polyvinylidene fluoride, aramid, polyethylene terephthalate, polytetrafluoroethylene, polyacrylonitrile, polyimide, polyamide, polyester and natural fiber.
[0145] A fifth aspect of the present invention provides an electrical device comprising the battery described in the fourth aspect. Specifically, the battery can serve as a power source for the electrical device or as an energy storage unit for the electrical device. The electrical device may include, but is not limited to, mobile devices (e.g., mobile phones, laptops), electric vehicles (e.g., pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks), electric trains, ships, satellites, and energy storage systems.
[0146] Below, the scheme of the present invention will be explained in conjunction with embodiment.It will be understood by those skilled in the art that the following examples are only used to illustrate the present invention and should not be regarded as limiting the scope of the present invention.In the embodiment, if specific technology or conditions are not indicated, the technology or conditions described in the literature in this area or the product instructions are used.The reagents or instruments used are not indicated by the manufacturer, and are all conventional products that can be obtained by commercial purchase.
[0147] Example 1
[0148]
【Na 2.04 Fe 1.9 Mg 0.1 (SO4) 3.02-z (SO3) z Preparation of @C
[0149] The inorganic reducing agent added is NaHSO3, and the conductive carbon selected is graphene nanosheets. The detailed preparation process is as follows:
[0150] Step 1: Weigh 0.04 mol of NaHSO3 reducing agent and add it to 1200 mL of deionized water. After rapid stirring, the dispersant is completely dissolved to form a reducing acidic solution.
[0151] Step 2: Weigh 20 g of graphene nanosheets and add them to the dispersant solution. After continuous stirring and ultrasonic dispersion, a suspension in which the graphene is evenly suspended is obtained.
[0152] Step 3: Weigh 1 mol of anhydrous Na2SO4, 1.9 mol of FeSO4·7H2O, and 0.1 mol of MgSO4·7H2O and slowly add them to the above suspension in sequence, and continue stirring until the above sulfate raw materials are completely dissolved to obtain a green graphene suspension;
[0153] Step 4: The suspension was spray-dried while continuously stirring at high speed. The air inlet temperature in the drying chamber of the equipment was set to 150°C, the air outlet temperature was maintained at 100°C, and the solution was added at a rate of 400 mL / h. After the spraying was completed, the spray material precursor to be sintered was directly collected.
[0154] Step 5: Place the spray material precursor in a tube furnace with dry inert gas continuously flowing in, raise the temperature to 380°C at a rate of 1.5°C / min, and keep it at 380°C for 12 hours to obtain the sodium ferrous sulfate carbon composite material of the above chemical formula type.
[0155]
Battery preparation
[0156] A membrane mixed with the prepared sodium ferrous sulfate carbon composite material, polyvinylidene fluoride (PVDF) and conductive carbon (mass ratio of 8:1:1) is used as the positive electrode, metallic sodium is used as the negative electrode, a glass fiber membrane is used as the separator, and a solution of 1 mol / L NaPF6 dissolved in ethylene carbonate / propylene carbonate (molar ratio of 1:1) is used as the electrolyte. They are assembled in an R2032 button battery shell to form a sodium ion battery.
[0157] The sodium ion batteries containing positive electrode active materials of Examples 2-10 and Comparative Examples 1-4 are the same as those of Example 1 except for different parameters (see Table 1 for details). The chemical formulas of the obtained positive electrode active materials are shown in Table 2.
[0158] Table 1
[0159]
[0160]
[0161] Table 1
[0162]
[0163] Table 1
[0164]
[0165]
[0166] In Table 1, “ / ” indicates that no addition was made.
[0167] Table 2
[0168] composition Example 1 <![CDATA[Na 2.04 Fe 1.9 Mg 0.1 (SO4) 3.02-z (SO3) z @C]]> Example 2 <![CDATA[Na 2.44 Fe 1.8 Ni 0.1 Zn 0.1 (SO4) 3.22-z (SO3) z @C]]> Example 3 <![CDATA[Na 2.66 Fe 1.8 Mn 0.2 (SO4) 3.33-z (SO3) z @C]]> Example 4 <![CDATA[Na 2.24 Fe 1.8 Mn 0.05 Mg 0.05 Zn 0.05 Co 0.05 (SO4) 3.12-z (SO3) z @C]]> Example 5 <![CDATA[Na 2.62 Fe 1.9 Cu 0.1 (SO4) 3.31-z (SO3) z @C]]> Example 6 <![CDATA[Na 1.94 Fe 1.8 Mg 0.2 (SO4) 2.97-z (SO3) z @C]]> Example 7 <![CDATA[Na 2.04 Fe 1.9 Mg 0.1 (SO4) 3.02-z (SO3) z @C]]> Example 8 <![CDATA[Na 2.04 Fe 1.9 Mg 0.1 (SO4) 3.02-z (SO3) z @C]]> Example 9 <![CDATA[Na 2.04 Fe 1.9 Mg 0.1 (SO4) 3.02-z (SO3) z @C]]> Example 10 <![CDATA[Na 2.04 Fe2(SO4) 3.02-z (SO3) z @C]]> Comparative Example 1 <![CDATA[Na 2.04 Fe 1.9 Mg 0.1 (SO4) 3.02-z (SO3) z @C]]> Comparative Example 2 <![CDATA[Na2Fe 1.9 Mg 0.1 (SO4)3@C]]> Comparative Example 3 <![CDATA[Na 2.4 Fe 1.9 Mn 0.1 (SO4) 3.2 @C]]> Comparative Example 4 <![CDATA[Na 2.16 Fe 1.9 Mg 0.1 (SO4) 3.08-z (SO3) z @C]]>
[0169] Testing and Analysis:
[0170] 1. Physical and chemical analysis was performed on the positive electrode active materials of Examples 1-10 and Comparative Examples 1-4, and the test results are shown in Table 3.
[0171] (1) The physical and chemical indicators of the positive electrode active material are observed by scanning electron microscopy to observe the morphology of the prepared samples;
[0172] (2) characterize the carbon content of the samples using thermogravimetric analysis;
[0173] (3) Use a laser particle size analyzer and a dry test process to test the average particle size D of the sample 50 and maximum particle size D 100 ;
[0174] (4) Using an X-ray diffractometer to obtain the XRD spectrum of the material to analyze the crystal structure and characteristic peak intensity of the sample;
[0175] (5) Use a specific surface area meter to test the specific surface area of the sample, and use potassium dichromate (K2Cr2O7) titration method to determine the Fe content in the sample 3+ Content (according to GB / T33828-2017).
[0176] 2. The electrochemical performance of the lithium-ion batteries of Examples 1-10 and Comparative Examples 1-4 was tested. Constant current charge and discharge tests were performed in the voltage range of 2.0-4.5 V and at current densities of 0.1 C and 1 C (1 C = 100 mAh / g), respectively, to obtain the specific capacity and cycle performance of the materials. The test results are shown in Table 3.
[0177] Table 3
[0178]
[0179] Result analysis:
[0180] The positive electrode active material in Example 1 was prepared by the method provided by the present invention. The SEM image of the spray material precursor obtained in this example is shown in FIG. Figure 1 , SEM images of the positive electrode active material are shown in Figure 2 , the corresponding XRD patterns are shown in Figure 3 After being placed in an open system for 24 hours, the XRD pattern of the material is shown in Figure 4 , combined with the data in Table 3 (I1 / I2, I 1’ / I 2’ , ΔI1 / I2) shows that the Fe in the positive electrode active material exists mainly in the form of Fe 2+ , and can remain unoxidized during long storage time, maintaining structural stability. The electrochemical performance of the battery containing it is shown in Table 3 and Figure 5-6 , indicating that the specific capacity and cycle stability of the battery can be improved. Similarly, Examples 2-10 also have the above advantages;
[0181] In addition, compared with Example 1, Example 7 increases the inlet air temperature, and its specific area reaches 22.2m 2 / g, such as Figure 7 Compared with Example 1, the obtained positive electrode active material has obvious surface pores, which may be caused by rapid dehydration. 50 The maximum particle size D is 7.8 μm. 100 The particle size is 23.1 μm, which is also larger than that of Example 1. Due to the large particle size, high specific surface area and irregular morphology, the material produces a significant gel phenomenon in the process of making electrode slurry due to its water absorption property, which affects the electrochemical properties of the material to a certain extent. The state of the gel is as follows: Figure 8 shown.
[0182] Comparative Example 1 Compared with Example 1, the sintering temperature in step 5 was increased. The results showed that the positive electrode active material contained a high content of Fe. 3+ , that is, the occurrence of ferrous phosphate side reaction cannot be suppressed;
[0183] Comparative Example 2 is compared with Example 1, in which no reducing agent is added. Figure 9 ) It can be seen that I1 / I2=0.85, indicating that the material components contain more Fe 3+Fe3O4 impurities. This is because under the high sintering conditions of 380℃, without the addition of reducing agent, the decomposition side reaction of Fe2SO4 is serious, resulting in a large amount of Fe3O4 impurities. The discharge capacity of the material at 0.1C is only 80.3mAh / g, and the capacity retention rate at 1C is 93.5%. In the absence of reducing agent protection, the electrochemical performance is significantly affected. The XRD pattern after standing ( Figure 10 ) shows that other impurities appear in the material after standing, indicating its poor storage performance;
[0184] Comparative Example 3 also did not add reducing agent, but lowered the sintering temperature, which reduced Fe 2+ However, the solid solution reaction of the low-temperature sintered material is incomplete, and a small amount of crystal water remains. The discharge capacity of the battery containing it is only 78.3mAh / g, and after 80 cycles of 1C charge and discharge, the capacity retention rate is only 92.3%. Moreover, after being placed under the same conditions, ΔI1 / I 2达 to 8.5%, indicating the poor storage properties of the lack of reducing agent materials;
[0185] Comparative Example 4 is compared with Example 1, in which the amount of reducing agent used is increased. Due to the excessive amount of reducing agent added, the consumption of reducing agent under N2 sintering conditions is less, resulting in the XRD pattern ( Figure 11 ), which has a negative impact on the electrochemical performance of the sample, with a 0.1C discharge capacity of only 81.3 mAh / g.
[0186] In the description of this specification, the reference terms "one embodiment", "some embodiments", "example", "specific example", or "some examples" mean that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art can combine and combine different embodiments or examples described in this specification and features of different embodiments or examples without contradiction.
[0187] Although the embodiments of the present invention have been shown and described above, it will be understood that the above embodiments are illustrative and are not to be construed as limitations on the present invention. A person skilled in the art may change, modify, replace and modify the above embodiments within the scope of the present invention.
Claims
1. A positive electrode active material, characterized in that: The positive electrode active material is an iron-based sulfate sodium ion battery positive electrode material, and the X-ray diffraction spectrum of the positive electrode active material has a first characteristic peak in the range of 34.9° to 35.3° and a second characteristic peak in the range of 35.3° to 35.5°; Wherein, the peak intensity I1 of the first characteristic peak and the peak intensity I2 of the second characteristic peak satisfy: 1.1≤I1 / I2≤1.5; The positive electrode active material has the chemical formula shown in formula (1): Na 2x Fe 2-y M y (SO4) (2+x-z) (SO3) z @C(1) Among them, 1≤x≤2.04; 0≤y≤0.2; 0<z≤0.04; M is selected from at least one of Mn, Co, Ni, Mg, Cu, and Zn.
2. The positive electrode active material according to claim 1, characterized in that The peak intensity of the first characteristic peak of the positive electrode active material after being left in an open environment at a temperature of 25° C. and a relative humidity of 30% for 24 hours is 1’ The peak intensity of the second characteristic peak I 2’ satisfy: 1.05≤I 1’ / I 2’ ≤1.4; 。 3. The positive electrode active material according to claim 2, characterized in that The peak intensity I1 of the first characteristic peak and the peak intensity I2 of the second characteristic peak satisfy: 1.2≤I1 / I2≤1.
4.
4. The positive electrode active material according to claim 2, characterized in that 1.1≤I 1’ / I 2’ ≤1.25; 。 5. The positive electrode active material according to claim 1, characterized in that The positive electrode active material satisfies at least one of the following conditions: The positive electrode active material D 50 4-10μm; The positive electrode active material D 100 Satisfy: 6μm<D 100 <20μm; The specific surface area of the positive electrode active material is 5-25 m 2 / g.
6. The positive electrode active material according to any one of claims 1 to 5, characterized in that The positive electrode active material has the chemical formula shown in formula (1): Na 2x Fe 2-y M y (SO4) (2+x-z) (SO3) z @C(1) Where 1≤x≤1.4; And / or, 0<z≤0.
03.
7. A method for preparing a positive electrode active material according to any one of claims 1 to 6, characterized in that: The preparation method comprises: (1) preparing a reducing agent solution, and mixing an inorganic conductive carbon material with the reducing agent solution to obtain a mixed solution 1; (2) mixing Na2SO4, FeSO4·7H2O and optional sulfate with the mixed solution 1 to obtain a mixed solution 2; (3) spray drying the mixed solution 2 to obtain a positive electrode active material precursor; (4) sintering the positive electrode active material precursor to obtain the positive electrode active material; Wherein, the reducing agent in the reducing agent solution is NaHSO3 and / or Na2S2O5; The sulfate is used to provide the M element, and the M element is selected from at least one of Mn, Co, Ni, Mg, Cu, and Zn.
8. The preparation method according to claim 7, characterized in that: In step (1), the mass of the solvent in the reducing agent solution is 2-3 times the mass of FeSO4·7H2O added in step (2).
9. The preparation method according to claim 7, characterized in that: In step (1), the inorganic conductive carbon material includes at least one selected from graphene, reduced graphene oxide, conductive graphite, acetylene black, Ketjen black, mesoporous carbon, and carbon nanotubes.
10. The preparation method according to claim 7, characterized in that: In step (2), the molar ratio of Na2SO4, FeSO4·7H2O and sulfate is δ:2-y:y; Among them, 0.96≤δ≤2; 0≤y≤0.
2.
11. The preparation method according to claim 7, characterized in that: The molar ratio of sodium element to Na2SO4 in the reducing agent is 2n:δ; Among them, 0<n≤0.
04.
12. The preparation method according to claim 7, characterized in that: In step (2), the mass ratio of the Na2SO4, FeSO4·7H2O and sulfate after complete dehydration to the inorganic conductive carbon material is 100:(0.5-10).
13. The preparation method according to claim 7, characterized in that: In step (3), the spray drying conditions include: The inlet air temperature is 130-160℃; the outlet air temperature is not less than 80℃.
14. The preparation method according to claim 7, characterized in that: In step (3), the cathode active material precursor D 50 4-10μm; The positive electrode active material precursor D 100 Satisfy: 6μm<D 100 <20μm.
15. The preparation method according to claim 7, characterized in that: In step (4), the sintering conditions include: sintering at 300-380° C. for 8-20 hours.
16. A positive electrode plate, characterized in that: The positive electrode sheet comprises the positive electrode active material according to any one of claims 1 to 6 or the positive electrode active material prepared by the preparation method according to any one of claims 7 to 15.
17. A battery, characterized in that: The battery comprises the positive electrode sheet according to claim 16.
18. An electrical equipment, characterized in that: Comprising the battery of claim 17.
Citation Information
Cited By
Positive electrode active material and preparation method therefor, positive electrode sheet, battery, and electric device
EP4723245A1
